2005
DOI: 10.1021/es050996j
|View full text |Cite
|
Sign up to set email alerts
|

Dried Sludges and Sludge-Based Chars for H2S Removal at Low Temperature:  Influence of Sewage Sludge Characteristics

Abstract: The use of sewage sludge as a precursor of adsorbent/ catalyst materials for environmental applications has been encouraged during the past few years. Due to the heterogeneous nature of sludges, there exists a lack of information regarding the characteristics of these low-cost precursors and how their physicochemical properties affect the final performance of materials prepared from them. In this work, three sewage-sludges collected at WWTPs with assorted sludge/wastewater treatment schemes were used as precur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
90
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(100 citation statements)
references
References 35 publications
(45 reference statements)
5
90
0
5
Order By: Relevance
“…Few studies compared the H 2 S removal efficiency of activated carbon in moist and dry conditions and revealed that humidity strongly promoted the adsorption efficiency of activated carbon [5,24,36]. The reaction mechanism in dry atmosphere with zeolite has recently been investigated [12], but still remains unclear with activated carbons.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies compared the H 2 S removal efficiency of activated carbon in moist and dry conditions and revealed that humidity strongly promoted the adsorption efficiency of activated carbon [5,24,36]. The reaction mechanism in dry atmosphere with zeolite has recently been investigated [12], but still remains unclear with activated carbons.…”
Section: Introductionmentioning
confidence: 99%
“…The efficient method of their industrial "recycling" and thus waste minimization is via pyrolysis, in which adsorbents are produced. It was recently demonstrated that such adsorbents can effectively remove dyes [13,19,20], heavy metals [13][14][15], phenols [13], or hydrogen sulfide [21][22][23][24][25][26][27]. Their high removal capacity is a result of complexity of surface chemistry, specific porosity, and high volume of mesopores.…”
Section: Introductionmentioning
confidence: 99%
“…That surface chemistry includes basic pH and presence of catalytic centers based on iron and other transition metals. These entities are formed as a result of solid state reactions during pyrolysis of complex inorganic/organic matrices [24,25,27]. Moreover, there is an indication that the pyrolysis conditions can be adjusted toward obtaining the most effective adsorbents for a desired application [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of surface reactions, H 2 S can be oxidized to either sulphur or SO 2 [8]. Activated carbons of different characteristics have also been prepared from sewage sludge pyrolysis or carbonization [10][11][12][13], obtaining pollutant removal results comparable to those corresponding to commercial catalytic activated carbons [13].…”
mentioning
confidence: 99%